2007
DOI: 10.3177/jnsv.53.372
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Sesame Seed Decreases Urinary Excretion of .ALPHA.- and .GAMMA.-Tocopherol Metabolites in Rats

Abstract: SummaryWe previously showed that dietary sesame seed and its lignan inhibited ␥ -tocopherol metabolism to 2,7,8-trimethyl-2(2 ′ -carboxyethyl)-6-hydroxychroman ( ␥ -CEHC), a ␥ -tocopherol metabolite, and markedly elevated tissue ␥ -tocopherol concentration in rats. The aim of this study was to clarify the effect of dietary sesame seed on ␣ -tocopherol metabolism. Vitamin E-deficient rats fed a vitamin E-free diet for 4 wk were fed a diet containing ␣ -tocopherol, ␣ -and ␥ -tocopherol, or ␣ -tocopherol with ses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 27 publications
2
6
0
Order By: Relevance
“…The urinary excretion of α-CEHC in the sesamin group was significantly lower compared to the α-TOH control group. Further, the combination of α-TOH and sesamin provoked a significant increase of hepatic α-TOH concentrations compared to α-TOH treated animals [95]. These observations have been confirmed in other animal studies [93,94].…”
Section: Intake Of Sesaminsupporting
confidence: 74%
See 2 more Smart Citations
“…The urinary excretion of α-CEHC in the sesamin group was significantly lower compared to the α-TOH control group. Further, the combination of α-TOH and sesamin provoked a significant increase of hepatic α-TOH concentrations compared to α-TOH treated animals [95]. These observations have been confirmed in other animal studies [93,94].…”
Section: Intake Of Sesaminsupporting
confidence: 74%
“…Sesamin is a lignan, a group of natural compounds derived from vegetable sources, like sesame seeds [92]. Sesamin is known as a natural inhibitor of the metabolism of TOH [93][94][95][96][97]. The cell regulatory actions of sesamin have been initially investigated in in vitro models, where Parker et al showed that sesamin acts as a selective inhibitor of CYP3A4, an initial enzyme of TOH metabolism [46].…”
Section: Intake Of Sesaminmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, we can conclude that CYP-dependent catabolism regulates the vitamin E concentration in the small intestine and in the liver. We previously found that sesame seed and its lignans, such as sesamin and sesaminol, inhibited vitamin E catabolism (13,23). These data suggest that dietary sesame seed enhances vitamin E absorption in the small intestine.…”
Section: Discussionmentioning
confidence: 89%
“…The increase of serum vitamin E after sesame seed supplementation has been reported in rats (Yamashita et al, 1995 ; Hanzawa et al, 2013 ). It has been suggested that sesame lignans regulate vitamin E metabolism by inhibiting tocopherol catabolism (Uchida et al, 2007 ; Hanzawa et al, 2013 ). However, other factors related to the effects of training on athlete's metabolism could have influenced the increase of vitamin E, once it was also observed in placebo group.…”
Section: Discussionmentioning
confidence: 99%